Incidence and Risk Factors of De novo Stress Urinary Incontinence after Pelvic Floor Reconstruction: A Nested Case-control Study - Shi-Yan Wang (Chinese Medical Journal, 2017)
Background: Some patients with pelvic organ prolapse may suffer from lower urinary tract symptoms (LUTS), especially stress urinary incontinence (SUI) named de novo SUI after pelvic floor reconstruction. This study aimed to investigate the incidence and risk factors of de novo SUI. Methods: This is a nested case-control study of 533 patients who underwent pelvic floor reconstruction due to pelvic organ prolapse (POP) at the Department of Gynecology in Peking University People's Hospital from January 2011 to March 2013. According to the inclusion and exclusion criteria, 401 patients were enrolled in the study with the follow-up rate of 74.8% (101 patients lost to follow-up). There were 75 patients with de novo SUI postoperatively. According to the ratio of 1:3, we ensured the number of control group (n = 225). The preoperative urinary dynamics, POP-quantification scores, and LUTS were compared between the two groups by univariate and multivariate logistic regression analyses to investigate the risk factors of de novo SUI. Results: The incidence of de novo SUI was 25% (75/300). Univariate analysis showed that the ratio of lower urinary tract obstruction (LUTO) before surgery in de novo SUI group was significantly higher than the control group (odds ratio [OR] = 2.1, 95% confidence interval [CI] [1.1–4.0], P = 0.022). The interaction test of LUTO and other factors displayed that Aa value was an interaction factor. With the increasing score of Aa, the incidence of de novo SUI become higher (OR = 2.1, 95% CI [1.0–3.7], P = 0.045). After multivariable adjustment, multiple regression analysis showed that LUTO was independently associated with a greater risk of de novo SUI after pelvic floor surgery (OR = 2.3, 95% CI [1.2–4.6], P = 0.013). Conclusions: Preoperative LUTO in patients with POP is a high-risk factor of de novo SUI, and high score of Aa-point is related to the occurrence of de novo SUI, which might be due to the outlet obstruction caused by bladder prolapse.